Alopecia: evaluation and treatment - Gordon KA; Tosti A (Dove Medical Press, 2011)
Katherine A Gordon, Antonella TostiDepartment of Dermatology and Cutaneous Surgery, University of Miami Miller School of Medicine, Miami, FL, USAAbstract: Hair loss is a very common complaint. Patients may describe increased shedding and diffuse or localized alopecia. The differential diagnosis of hair loss includes a number of disorders causing cicatricial or noncicatricial alopecias. This paper describes the clinical approaches and diagnostic tests that are useful in the evaluation of patients presenting with alopecia. It also reviews treatments for noncicatricial alopecias, including androgenetic alopecia, alopecia areata, and telogen effluvium, as well as cicatricial alopecias, including lichen planopilaris, its clinical variant frontal fibrosing alopecia, and discoid lupus erythematosus.Keywords: alopecia, evaluation, treatment